Mababang paaralan - Balagot, Gerniña Castro
Form: Documentary, Medium: Video, Estimated Length: 24 minutes. The educational system cannot move forward because the problem lie in the grassroots level. The Philippine government does not appropriate the necessary funds to deliver basic services, that of providing and promoting quality public education, to its citizens. These bear profound effects on the school where the optimum level of providing quality education is fully rendered. The documentary then aims to present the disparity between the ideals of public education and the reality in most Philippine public schools while giving light to the manner by which the school continues with the attempt to provide quality education to its students. The documentary adopts the observational mode of representation that encompasses a calendar of significant and interesting events in Bolingit Elementary School. The focus of the documentary is on the activities of the teacher and her class to create an awareness of the real state of public education in one elementary school. Hampered with inadequate resources for education, the teacher and her students have to contend with constraints of crowded classrooms, lack o textbooks and substandard facilities and equipment. The experiences of the teacher and her students, the varied roles they assume and the ways in which they respond to certain features of the school influences much of what occurs in the documentary. Images are recorded as they happen. This will afford the viewer to take a look into the conditions in one public school which are probably replicated in many other Philippine public schools.